Preliminary study on the presence of aflatoxin B1 in feeds for lactating cows sampled in the Parmigiano Reggiano production area - A. Zaghini; M. Ligabue; E. Bortolazzo; M. Montagner (Italian Journal of Animal Science, 2010)
Toxigenic fungi can affect the most common and relevant crops during the growth, harvest, or storage steps and produce toxic substances known as mycotoxins. Among the reasons for which these substances contaminate approximately 25% of the world’s food crops (Lawlor and Lynch, 2001) are prominently inappropriate agricultural and storage practices, intercontinental shipping, as well as environmental and climatic conditions (relative humidity and temperature) (Moss, 1991).